Sustaining Biological and Cultural Diversity - Ana G. Valenzuela Zapata; Marie Sarita Gaytán (Revue d'ethnoécologie)
Outlined by the World Trade Organization, Geographical Indication (GI) designations identify specific quality guidelines and protect foods, drinks, and other products from competition based on their specific geographical origin or location. In Mexico, GIs are known as Denominations of Origin (DO), and in 1974, tequila was recognized as Mexico’s first DO product. In 1994, the Mexican government established the DO for the distilled agave drink category, mezcal. Within the western state of Jalisco, Mexico, there are several different types of mezcal, however only a few are classified under DO regulations. Although handcrafted in Jalisco for centuries, many mezcals, like raicilla, are unprotected under the current DO system. Traditional manufacturers, who are often themselves agave farmers, play an important role in the maintenance of the region’s ecological resources. Focusing on three drinks (tequila, raicilla, and mezcal), each produced in Jalisco, Mexico, we analyze how various social actors negotiate issues pertaining to biodiversity. In particular, we call attention to artisan craftsmanship and the human traditions that characterize sustainability. Further, we focus on a range of agave species (wild and cultivated), used by both large and small scale producers, in relation to agave diversity and conservation efforts in the distilled spirits market. Specifically, we ask the following questions : What agave species are currently used by both large and small scale manufacturers of tequila and mezcal in the state of Jalisco? What conditions enable the incorporation of more bio-diverse species and native landraces? As we show, artisanal producers are more likely to use diverse species of agave in the manufacture of their distilled drinks. Pressures to modernize their methods of production threaten the ecological and cultural diversity of regional Jaliscan products.